2013
DOI: 10.1093/scan/nst067
|View full text |Cite
|
Sign up to set email alerts
|

From neural signatures of emotional modulation to social cognition: individual differences in healthy volunteers and psychiatric participants

Abstract: It is commonly assumed that early emotional signals provide relevant information for social cognition tasks. The goal of this study was to test the association between (a) cortical markers of face emotional processing and (b) social-cognitive measures, and also to build a model which can predict this association (a and b) in healthy volunteers as well as in different groups of psychiatric patients. Thus, we investigated the early cortical processing of emotional stimuli (N170, using a face and word valence tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
71
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(79 citation statements)
references
References 107 publications
7
71
0
Order By: Relevance
“…In agreement with previous studies (e.g. Torralva et al [5]), we found that both ADHD and BD subjects showed deficits in verbal memory and executive function [4,5,6,28]. Attentional lapses and performance variability [50] are core characteristics of ADHD that may be related to DMN abnormalities [51,52].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with previous studies (e.g. Torralva et al [5]), we found that both ADHD and BD subjects showed deficits in verbal memory and executive function [4,5,6,28]. Attentional lapses and performance variability [50] are core characteristics of ADHD that may be related to DMN abnormalities [51,52].…”
Section: Discussionsupporting
confidence: 92%
“…The frequent co-occurrence of bipolar disorder (BD) and attention deficit/hyperactivity disorder (ADHD) in adults usually manifests itself as shared clinical symptoms [1,2,3] and similar cognitive impairments [4,5,6]. It is therefore an important scientific and medical challenge to develop novel physiological markers to thoroughly differentiate these disorders from one another.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, siblings were less able to correctly recognize three kinds of facial expression compared to the healthy controls, but this difference was not statistically significant. Ibanez et al also found that the accuracy of facial expression recognition showed a poorer, but non-significant performance in relatives of patients with schizophrenia compared to controls [26]. The siblings, who are at higher risk of developing schizophrenia, may have some degree of impairment in facial expression recognition but the ethology results may be harder to detect.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they provide new evidence for the interaction among low and high-level cognition, emotion, and social domains (Moll and Schulkin, 2009; Pessoa, 2009; Alguacil et al, 2013; Ibanez et al, 2013, 2014; Ruz et al, 2013; Baez et al, 2014b). In the same vein, part of the evidence presented shows that our emotional arousal biases our decisions in the social world (Beauregard, 2007; Heatherton, 2011).…”
Section: Discussionmentioning
confidence: 99%